2010
DOI: 10.1063/1.3462916
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polarization fields on carrier lifetime and recombination rates in InGaN-based light-emitting diodes

Abstract: We study differential carrier lifetimes in InGaN light-emitting diodes ͑LEDs͒ of varying wavelengths. Increase in wavelength is correlated with an increase in lifetime, due to the impact of the polarization fields on carrier overlap. This effect explains the early onset of droop in longer-wavelength LEDs.Efficiency droop is a nonthermal process of disputed origin which quenches the internal quantum efficiency ͑ IQE ͒ of GaN-based light-emitting diodes ͑LEDs͒ at high current density ͑J͒. One point of particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(110 citation statements)
references
References 7 publications
10
99
1
Order By: Relevance
“…Our present results show that the rate of decrease of the Auger coefficient with density in the 2 × 10 18 − 5 × 10 19 cm −3 range (which includes the peak of the internal quantum efficiency of LEDs [9]) is smaller than the rate of decrease of the radiative coefficient (B) [36]. The more rapid decrease of the B coefficient in comparison to the C coefficient with increasing free-carrier density may explain the asymmetry of the internal quantum efficiency curve reported in the literature [68], without invoking an additional fourth-order or higher-power carrier-loss mechanism.…”
Section: Due To (A) Electron-electron-hole (E-e-h) and (B) Hole-hole-mentioning
confidence: 85%
See 2 more Smart Citations
“…Our present results show that the rate of decrease of the Auger coefficient with density in the 2 × 10 18 − 5 × 10 19 cm −3 range (which includes the peak of the internal quantum efficiency of LEDs [9]) is smaller than the rate of decrease of the radiative coefficient (B) [36]. The more rapid decrease of the B coefficient in comparison to the C coefficient with increasing free-carrier density may explain the asymmetry of the internal quantum efficiency curve reported in the literature [68], without invoking an additional fourth-order or higher-power carrier-loss mechanism.…”
Section: Due To (A) Electron-electron-hole (E-e-h) and (B) Hole-hole-mentioning
confidence: 85%
“…for E gap = 3.5 eV) and the corresponding coefficients cannot account for the experimentally measured values in nitride devices (10 −31 -10 −30 cm 6 s −1 ) [3][4][5][6][7][8][9][10][11]. The coefficients increase drastically for decreasing band-gap values in the range of 2.4-3.5 eV, which is the typical band-gap range for nitride devices.…”
Section: A Direct Auger Recombination In Ganmentioning
confidence: 90%
See 1 more Smart Citation
“…This removes the problem that arises in CW photoluminescence (PL) and electroluminescence (EL) experiments that under steady-state excitation conditions the equilibrium carrier densities in c-plane and m-plane structures can be very different due to the dependence on the different recombination rates. The importance of the role of the recombination rate in determining droop, hence excited carrier density, has already been shown by David et al 29 for polar InGaN LEDs with varying In fraction. In this work, it was shown that decreases in the recombination rate as the In fraction increased lead to the occurrence of efficiency droop at progressively lower current densities.…”
mentioning
confidence: 76%
“…The pump pulse power was scaled with the photon energy between 0.60 and 0.68 nJ, corresponding to an average photoexcited carrier density of 1 × 10 18 cm −3 . For such carrier densities, hot carrier generation related to Auger recombination can safely be ignored [17].…”
Section: Methodsmentioning
confidence: 99%